Towards Sustainable Energy: Evidenced-Based Practices in Implementing Renewable Energy Projects (American Journal of Multidisciplinary Research and Innovation, 2025)
The research examined the effectiveness, challenges, and lessons gained from renewable energy (RE) project implementation across different global areas. It analyzed business models, government investment policies, and their influence on education, the environment, tourism, and health. The research explores the impact of incentive policies, governance effectiveness, financing mechanisms, and net metering on RE adoption. The study utilizes a qualitative systematic literature review (SLR) of research published between 2019 and 2024, analyzing 134 relevant studies. Results showed that RE projects foster sustainability in education, promote environmental responsibility, and provide financial and environmental benefits to educational institutions. Environmental sustainability, together with economic growth, regional development, and energy independence, serves as a result of renewable energy projects in the tourism industry that make the sector resilient and sustainable. Through environmental projects, RE reduces carbon dioxide emissions while improving air quality, leading to diminished respiratory health issues. These initiatives play a key role in economic development, job creation, energy security, sustainable global growth, and environmental stewardship. The study concludes that an integrated approach that includes best practices, policy support, and collaborative efforts is central to driving the transition to a more sustainable and resilient energy future. The findings of the study can help policymakers decide on the appropriate policy, plans, and programs for a just energy transition.